Reader's Digest the truth about history : how new evidence is transforming the story of the past - Miller, Russell; Reader's Digest Association; Planet Three Publishing Network (London ; Sydney : Reader's Digest Association, 2004)
1. History--Miscellanea. 2. Histography. 3. Curiosity and wonders.
Includes index.
Basic Ed. Students
Keywords: History -- Miscellanea; Historiography; Curiosity and wonders